👤

45-2×{17+14:[27-(15+a)]-3}=3

Răspuns :

45 - 2 × { 17 + 14 : [ 27 - ( 15 + a ) ] - 3 } = 3

2 × { 17 + 14 : [ 27 - ( 15 + a ) ] - 3 } = 45 - 3

2 × { 17 + 14 : [ 27 - ( 15 + a ) ] - 3 }  = 42

17 + 14 : [ 27 - ( 15 + a ) ] - 3 = 42 : 2

17 + 14 : [ 27 - ( 15 + a ) ] - 3 = 21

17 + 14 : [ 27 - ( 15 + a ) ]  = 21 + 3

14 : [ 27 - ( 15 + a ) ]  = 24 - 17

14 : [ 27 - ( 15 + a ) ] = 7

27 - ( 15 + a ) = 14 : 7

27 - ( 15 + a ) = 2

15 + a = 27 - 2

15 + a = 25

a = 25 - 15

a = 10 → numarul, aflat prin metoda mersului invers